The extent of accessibility of microfinance services by SMEs owned by Women - Taonga N/A Kueredza (Indonesian Journal Of Business And Economics, 2022)
This study sought to establish the extent of accessibility of microfinance services by Women SMEs in Zimbabwe. There is a growing importance and contribution of women-owned Small and Medium enterprises (SMEs) to economies’ in the world to their economic growth and employment creation. However, the majority of SMEs continue to face constraints in their access to resources, and women-owned SMEs are not spared resulting in entrepreneurial gender financing gap. This study’s purpose was to develop a framework for enhancing access to finance from microfinance institutions (MFIs) to women-owned small and medium enterprises (SMEs) in Harare, Zimbabwe. This study was motivated by the inadequacies in the frameworks existing in both developed and developing countries including Zimbabwe, that holistically address enhanced financial access to credit from MFIs by women-owned SMEs. A cross-sectional, mixed method study was employed with both quantitative and qualitative methods being utilised. The collected quantitative data were analysed using factor analysis with the help of Statistical Package for Social Sciences (SPSS version 26) while qualitative data was analysed using thematic analysis with the help of NVivo (version 11). The key findings that comprised the developed framework of enhanced financial access from MFIs by women-owned SMEs revealed that facilitating factors are: women SME support systems, efficient infrastructure, collaborations, and regulated interest rates. On financial access constraints faced by women-owned SMEs, the findings are; women SME’s informality, inadequate infrastructure, MFI’s prohibitive charges, poor financial position, illiteracy, non-sensitised MFI products and services, stereotyping and lack of collateral. Lastly, the appropriate and affordable financial products and services at the women SMEs’ disposal are MFIs’ innovative products and services, sufficiently capitalised MFIs, capacity building, business capital, micro-Insurance, group loans, financial literacy and business start-up coaching, online applications and government support. The study developed a framework that assists MFIs and women-owned SMEs to enhance accessibility to finance between them. The framework informs policy that achieves gender responsiveness, equality and equity for both male and female entrepreneurial financing initiatives for an inclusive and sustainable economic growth and development.Keywords: Microfinance, Accessibility, Microfinance institutions, Women-owned small and medium enterprises, Microfinance products and services